Daftar Isi - , No 2 (2014): Oktober 2014, Vol 7 (Jurnal Energi Dan Manufaktur; Vol 7 No 2 (2014): Oktober 2014, 2015)
Link Vol 7, No 2 (2014): Oktober 2014: http://www.mediafire.com/view/n9gzbq2z3nwol5v/JEM_Vol._7_No_2_2014.pdf